Sensing performance optimization by tuning surface morphology of organic (D-π-A) dye based humidity sensor - Al-Sehemi, A.G.; Al-Assiri, M.S.; Kalam, A.; Zafar, Q.; Azmer, M.I.; Sulaiman, Khaulah; Ahmad, G. (Elsevier, 2016)
We present herein the effect of varied humidity levels on the electrical parameters of the (E)-2-{4-[2-(3,4,5-trimethoxybenzylidene) hydrazinyl]phenyl}ethylene-1,1,2-tricarbonitrile (TMBHPET) organic dye based humidity sensor. TMBHPET dye has been synthesized bearing an additional methoxy group substituent at the terminal benzene ring of previously reported (E)-2-(4-(2-(3,4-dimethoxybenzeylidene)hydrazinyl)phenyl)ethane-1,1,2-tricarbonitrile (DMBHPET) dye. The strategic dye design is believed to increase the π-electron polarizability in the dye structure. Capacitive type humidity sensor has been fabricated in planar geometry of Al/TMBHPET/Al and its capacitance has been monitored as a function of relative humidity (RH) level at varied frequencies of ∼1 v AC input bias. A maximum sensitivity ∼46 fF/%RH at 1 kHz has been observed which is almost seven times higher as that of DMBHPET based humidity sensor which may be attributed to the porous surface morphology of TMBHPET sensing film. The sensor has also shown reversible changes in its capacitance with variation in humidity level and hysteresis value has been observed to be 2.4%. The motive of the present study was to increase the sensing parameters of the previously reported humidity sensor utilizing DMBHPET dye, which has been successfully achieved.